Kanssatutkimus Ihanteet ja käytännöt - Bettin, Caterina (Tampere University Press, 2023)
Participatory approaches and co-research are increasingly employed in the current moment for exploring barriers to equality. Co-research treats research participants as experts in their own lives and as equal research partners. Research conducted with this orientation is based on research problems drafted by the research participants themselves from their aspirations regarding the research process and an active partnership that considers the interests of all parties involved. Participatory methods are used in co-research, particularly for the purpose of deepening the contextualisation of research knowledge about structurally vulnerable or subordinated groups and to challenge the power positions associated with traditional research designs. In co-research, the role of the people involved in the research is more central than in more traditional research. One of the key principles of co-research is that co-investigators (a) can participate in various roles, (b) have the opportunity to participate in different phases of the research according to their own interests and resources, and (c) co-investigators' participation can take many forms, including differences in intensity. The idea is to provide more people with opportunities to contribute to the knowledge production about themselves and their communities from their respective perspectives and interests. Co-research is also seen as an opportunity to improve the relevance and usefulness of scientific knowledge. It aims to genuinely increase interaction and openness and extend science's societal responsibility. In this book, we approach co-research as a means to promote social justice, as an action with a societal impact contributor to social impact and as a means to promote the societal responsibility of science. We discuss and evaluate the ideals of the co-research process concerning the everyday challenges and practices in research. Above all, we offer the knowledge and experience generated by our own projects to support those planning or already implementing co-research projects.